2022
DOI: 10.1093/europace/euac056
|View full text |Cite|
|
Sign up to set email alerts
|

The GermAn Laser Lead Extraction RegistrY: GALLERY

Abstract: Aims The GermAn Laser Lead Extraction GallerY (GALLERY) is a retrospective, national multicentre registry, investigating the safety and efficacy of laser lead extraction procedures in Germany. Methods and results Twenty-four German centres that are performing laser lead extraction have participated in the registry. All patients, treated with a laser lead extraction procedure between January 2013 and March 2017, were consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
4
24
1
Order By: Relevance
“…17 Additionally, as proved by The GermAn Laser Lead Extraction RegistrY: GALLERY a lead dwell time ≥10 years was identified as an independent risk factor for procedural failure during laser lead extraction. 18 As observed by Nir Levi et al in lead fixation mechanism impacts outcome of TLE: data from the European Lead Extraction ConTRolled Registry: older age of ICD leads, a higher percentage of passive-fixation leads, and dual-coil ICD leads contributed to longer fluoroscopy time during extraction of ICD leads in group A compared with group B (3.3 min vs. 1.4 min, P < 0.001). 19 Additionally, in our study with 23 Sprint Fidelis leads, we observed complete procedural success in all cases with no major complications or procedure-related deaths regardless of the method of extraction.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…17 Additionally, as proved by The GermAn Laser Lead Extraction RegistrY: GALLERY a lead dwell time ≥10 years was identified as an independent risk factor for procedural failure during laser lead extraction. 18 As observed by Nir Levi et al in lead fixation mechanism impacts outcome of TLE: data from the European Lead Extraction ConTRolled Registry: older age of ICD leads, a higher percentage of passive-fixation leads, and dual-coil ICD leads contributed to longer fluoroscopy time during extraction of ICD leads in group A compared with group B (3.3 min vs. 1.4 min, P < 0.001). 19 Additionally, in our study with 23 Sprint Fidelis leads, we observed complete procedural success in all cases with no major complications or procedure-related deaths regardless of the method of extraction.…”
Section: Discussionmentioning
confidence: 70%
“… 17 Additionally, as proved by The GermAn Laser Lead Extraction RegistrY: GALLERY a lead dwell time ≥10 years was identified as an independent risk factor for procedural failure during laser lead extraction. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown a treatment algorithm for patients with device endocarditis requiring lead removal, pacemaker dependency and atrial fibrillation. Systemic device related infection represents a rare but serious complication of device therapy, associated with significant morbidity and mortality (10). In systemic device related infection, extraction of all lead material is recommended as a class I indication (11).…”
Section: Discussionmentioning
confidence: 99%
“…2 Major TLE procedural complications, including death, occur in 1%-2% of cases, and superior vena cava (SVC) tears have been reported in up to 1.8%. 1,3 Some authors suggest that risk factors for SVC tears are:…”
Section: Introductionmentioning
confidence: 99%
“…female sex, ICD leads and they may be more common with the use of laser sheaths. 3,4 Laceration of the SVC is the most lethal complication during TLE with a mortality as high as 50%. 5,6 Since rapid surgical intervention is required, a heart team approach is essential to handle this rare but potentially lethal complication.…”
Section: Introductionmentioning
confidence: 99%